"I made a mistake!": A narrative analysis of experienced physicians' stories of preventable error. Issue 2 (5th January 2021) - Kandasamy, Sujane; Vanstone, Meredith; Colvin, Eamon; Chan, Teresa; Sherbino, Jonathan; Monteiro, Sandra
Abstract: Rationale, aims, and objectives: The complexity of healthcare systems makes errors unavoidable. To strengthen the dialogue around how physicians experience and share medical errors, the objective of this study was to understand how generalist physicians make meaning of and grow from their medical errors. Methods: This study used a narrative inquiry approach to conduct and analyse in‐depth interviews from 26 physicians from the generalist specialties of emergency, internal, and family medicine. We gathered stories via individual interview, analysed them for key components, and rewrote a "meta‐story" in a chronological sequence. We conceptualized the findings into a metaphor to draw similarities, learn from, and apply new principles from other fields of practice. Results: Through analysis we interpreted the story of a physician who is required to make numerous decisions in a short period of time in different clinical environments among the patient's family and whilst abiding by existing rules and regulations. Through sharing stories of success and failure, the clinical supervisor can help optimize the physician's emotional growth and professional development. Similarly, through sharing and learning from stories, colleagues and trainees can also contribute to the growth of the protagonist's character and the development of clinic, hospital, and healthcare system. Conclusion: We draw parallels between the clinical setting and a generalist physician's experiences of a medical error with the environment and practices within professional sports. Using this comparison, we discuss the potential for meaningful coaching in medical education.